Genome sequence and analysis of resistance and virulence determinants in a strain of Neisseria mucosa causing native-valve endocarditis. Issue 3 (June 2015) - Hollenbeck, Brian L; Gannon, Stephen; Qian, Qinfang; Grad, Yonatan
Abstract : Introduction: Neisseria mucosa colonizes mucosal surfaces in humans and can serve as a reservoir for resistance and virulence determinants for Neisseria meningitidis and Neisseria gonorrhoeae, but only on rare occasions has this species been documented as a cause of invasive infection. The host and pathogen factors that predispose to invasive infection with this organism are unknown. Case presentation: A healthy 27-year-old female presented with fever. N. mucosa was isolated from two sets of blood cultures drawn on arrival. Transoesophageal echocardiogram revealed mitral valve vegetation. The patient was diagnosed with endocarditis by modified Duke's criteria. Genome sequencing was performed on the isolate and comparison was made with previously published Neisseria resistance and virulence determinants. Although putative virulence factors were present in this isolate, there is not a sufficient database of genetic information for this species to reach conclusions about the role of these virulence factors in predisposing to invasive disease. Conclusions: For rare infections, like this case, only through reporting of the clinical course and pathogen genome can a sufficient dataset accumulate to make statistically significant inferences and to motivate hypothesis-based confirmatory experiments. This is the first report of whole genome sequencing for this species to be accompanied by a description of invasive clinical disease, and sets the precedent for future studies.